Collagenase unwinds triple-helical collagen prior to peptide bond hydrolysis - Chung, Linda (Nature Publishing Group, 2004)
Breakdown of triple-helical interstitial collagens is essential in embryonic development, organ morphogenesis and tissue remodelling and repair. Aberrant collagenolysis may result in diseases such as arthritis, cancer, atherosclerosis, aneurysm and fibrosis. In vertebrates, it is initiated by collagenases belonging to the matrix metalloproteinase (MMP) family. The three-dimensional structure of a prototypic collagenase, MMP-1, indicates that the substrate-binding site of the enzyme is too narrow to accommodate triple-helical collagen. Here we report that collagenases bind and locally unwind the triple-helical structure before hydrolyzing the peptide bonds. Mutation of the catalytically essential residue Glu200 of MMP-1 to Ala resulted in a catalytically inactive enzyme, but in its presence noncollagenolytic proteinases digested collagen into typical 3/4 and 1/4 fragments, indicating that the MMP-1(E200A) mutant unwinds the triple-helical collagen. The study also shows that MMP-1 preferentially interacts with the α2(I) chain of type I collagen and cleaves the three α chains in succession. Our results throw light on the basic mechanisms that control a wide range of biological and pathological processes associated with tissue remodelling.